2013
DOI: 10.1186/1471-2164-14-177
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes from Trichoderma harzianum during growth on cell wall of Fusarium solanias a tool for biotechnological application

Abstract: BackgroundThe species of T. harzianum are well known for their biocontrol activity against many plant pathogens. However, there is a lack of studies concerning its use as a biological control agent against F. solani, a pathogen involved in several crop diseases. In this study, we have used subtractive library hybridization (SSH) and quantitative real-time PCR (RT-qPCR) techniques in order to explore changes in T. harzianum genes expression during growth on cell wall of F. solani (FSCW) or glucose. RT-qPCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 36 publications
5
59
0
1
Order By: Relevance
“…This fact is consistent with the extensive metabolic activity expected for a filamentous fungus growing on a rich medium (glucose 2% medium) with an easily assimilable substrate [17]. Under this culture condition up-regulation of a specific subset of oxidoreductases and nucleotide binding proteins endoding genes related to primary metabolism is commonly observed for Trichoderma species, which are down-regulated in the presence of complex substrates [13]. Vieira et al in 2013 showed the same pattern of repressed categories when T. harzianum was grown on Fusarium solani cell wall, suggesting that this result is not pathogen-dependent.…”
Section: Resultssupporting
confidence: 84%
“…This fact is consistent with the extensive metabolic activity expected for a filamentous fungus growing on a rich medium (glucose 2% medium) with an easily assimilable substrate [17]. Under this culture condition up-regulation of a specific subset of oxidoreductases and nucleotide binding proteins endoding genes related to primary metabolism is commonly observed for Trichoderma species, which are down-regulated in the presence of complex substrates [13]. Vieira et al in 2013 showed the same pattern of repressed categories when T. harzianum was grown on Fusarium solani cell wall, suggesting that this result is not pathogen-dependent.…”
Section: Resultssupporting
confidence: 84%
“…Primers were designed with redundancy to complement the identified conserved sequence homology that spanned between 100 and 150 bp in order to account for strain-strain differences. Primer sets for chitinase 33 , were chosen because it is a chitinase that lacks a substrate-binding domain and has been shown to be involved in mycoparasitism [30, 31]. The primer set for qid74 was selected because it was shown to mediate hydrophobic surface attachment during mycoparasitism [32].…”
Section: Methodsmentioning
confidence: 99%
“…Primer sets for chitinase 33 , were chosen because it is a chitinase that lacks a substrate-binding domain and has been shown to be involved in mycoparasitism [30, 31]. The primer set for qid74 was selected because it was shown to mediate hydrophobic surface attachment during mycoparasitism [32]. For quantification purposes, each target was normalized to the 18S gene using previously published methods [33].…”
Section: Methodsmentioning
confidence: 99%
“…The subtilisin serine protease gene Spm 1 from T. asperellum T4 was all up-regulated in response to different fungal phytopathogen induction Liu et al, 2010 . The transcription of serine protease gene in T. harzianum was up-regulated under Fusariura solani cell walls treatment Vieira et al, 2013 . Northern blot analysis indicated that the serine protease gene SL41 from T. harzianum T88 could be induced by phytopathogenic fungi cell walls and the protease SL41 from T. harzianum T88 exerted broad-spectrum antifungal activity against phytopathogenic fungi Liu and Yang, 2013 .…”
Section: Differential Expression Analysis Of Tghss42 In T Ghanensementioning
confidence: 96%